Dialoque between Allah and iblis in the qur'an - Zarasi, Mohammad (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2013)
This library-oriented research examined the dialogue between Allah and Iblīs in the Qurʼān. The composition and form of the dialogue were evaluated in this study. The whole discussion between Allah and Iblīs were encapsulated in one exchange and then some important statistics were indicated about the words and sentences in this. Moreover, the essential principles of the dialogue were illustrated and this categorized in the Qurʼān based on its unique characteristics. This dialogue was compared and contrasted with similar ones in Judaism, Christianity and Zoroastrianism. Lessons obtained from the dialogue were then discussed. The verses from when the angels and Iblīs were commanded to bow down until the concluding words of Allah were elaborated: the refusal of Iblīs, the inquiry of Allah on the disobedience of Iblīs, the reactionary answer and expulsion of Iblīs from heaven, the request of Iblīs, the approval of respite for Iblīs, the final words of Iblīs, the revengeful vows and the destiny of Iblīs were widely explained. The study concludes that the dialogue between Allah and Iblīs was a revolutionary turning point in the history of man, and it tremendously determined the fundamental outlook of the life of man. A variety of principles, characteristics and teachings, in addition to its own specific form, distinguishes this dialogue from others in the Qurʼān. This is more apparent when the dialogue in the Qurʼān was more organized and conductive in comparison with similar dialogues between Allah and Satan in other religions.